Study protocol: healthy urban living and ageing in place (HULAP): an international, mixed methods study examining the associations between physical activity, built and social environments for older adults the UK and Brazil - Geraint Ellis; Ruth F. Hunter; Adriano Akira F. Hino; Claire L. Cleland; Sara Ferguson; Brendan Murtagh; Ciro Romelio Rodriguez Anez; Sara Melo; Mark Tully; Frank Kee; Urmi Sengupta; Rodrigo Reis (BMC, 2018)
Abstract Background The ability to 'age in place' is dependent on a range of inter-personal, social and built environment attributes, with the latter being a key area for potential intervention. There is an emerging body of evidence that indicates the type of built environment features that may best support age friendly communities, but there is a need to expand and consolidate this, while generating a better understanding of how on how research findings can be most effectively be translated in to policy and practice. Methods The study is based on two case study cities, Curtiba (Brazil) and Belfast (UK), which have highly contrasting physical, social and policy environments. The study deploys a mix methods approach, mirrored in each city. This includes the recruitment of 300 participants in each city to wear GPS and accelerometers, a survey capturing physical functioning and other personal attributes, as well as their perception of their local environment using NEWS-A. The study will also measure the built environments of the cities using GIS and develop a tool for auditing the routes used by participants around their neighbourhoods. The study seeks to comparatively map the policy actors and resources involved in healthy ageing in the two cities through interviews, focus groups and discourse analysis. Finally, the study has a significant knowledge exchange component, including the development of a tool to assess the capacities of both researchers and research users to maximise the impact of the research findings. Discussion The HULAP study has been designed and implemented by a multi-disciplinary team and integrates differing methodologies to purposefully impact on policy and practice on healthy ageing in high and low-middle income countries. It has particular strengths in its combination of objective and self-reported measures using validated tools and the integration of GPS, accelerometer and GIS data to provide a robust assessment of 'spatial energetics'. The strong knowledge exchange strand means that the study is expected to also contribute to our understanding of how to maximise research impact in this field and create effective evidence for linking older adult's physical activity with the social, built and policy environments.